Understanding Education Technology Integration Experiences among Engineering Educators: A Cultural Historical Activity Theory Approach - Cawood, Ka Wai (School of Education, 2021)
Although the University of Cape Town has implemented various education technology projects in the last two decades, the disruptions experienced during the #FeesMustFall movement and the COVID-19 pandemic point to challenges with integrating technology successfully, highlighting the need to better understand technology integration in higher education. Based in the Engineering Faculty, I adopted a Cultural Historical Activity Theory (CHAT) perspective to understand the experiences of engineering educators with regards to education technology integration in a department. A qualitative case study with semi-structured interviews was conducted with engineering educators. The data was analysed according to the categories in CHAT. Individual educator analyses were presented as activity systems. These were then synthesised to a departmental level understanding. I found that all educators integrated education technology to varying degrees. These included the university's learning management system, Microsoft PowerPoint, document cameras, and various engineering technologies. Educators integrated education technology to improve the practical demonstration of engineering concepts, prepare students for the workplace, and improve the efficiency of certain tasks. Their integration efforts were mediated mainly by the university's infrastructure and their access to institutional technologies. Nondirective approach by the departmental and faculty leadership provided educators with the freedom to integrate education technology, although, some educators expressed a desire for increased leadership intervention. Technical and pedagogical support services from the university provided resources and support for integration. The technologies integrated by the educators were informed by their preference for teaching resources that visualised theory. Educators were concerned with the impact of lecture recording on attendance, highlighting sustainability issues of this technology. As all participants integrated education technology independently, future studies may benefit from understanding less active users' experiences, the contribution of support services, and the role of departmental leadership.